Avaliação fármaco-toxicológica da molécula JM-20 em Caenorhabditis elegans - Silva, Aline Franzen da (2023)
With the discovery of new molecules with pharmaceutical potential, studies examining different mechanisms of action and toxicological aspects emerge. The 3-ethoxycarbonyl-2-methyl-4-(2-nitrophenyl)-4,11-dihydro-1H-pyrido[2,3-b][1,5]benzodiazepine (JM-20) is a hybrid compound derived from 1,5-benzodiazepines, structurally distinguished by the addition of 1,4-dihydropyridine linked to the benzodiazepine ring. This modification gives this molecule the potential for neuroprotective, antioxidant, and anxiolytic activity. Given its potential as a promising multi-target molecule, further studies are needed to deepen the understanding of its mechanism of action. In this study, the Caenorhabditis elegans (C. elegans) experimental model was used to investigate the effects of chronic treatment with JM-20. Animals from the wild-type strain (N2) and CB156 mutants (unc-25) were subjected to chronic treatment with concentrations ranging from 0 to 100 μM of JM-20. The results indicated that JM-20 did not result in mortality, but at the higher concentrations evaluated, there was a delay in worm development after 48 hours of exposure. Behavioral analyses revealed a decrease in the defecation cycle. Furthermore, an increase in locomotor activity and a reduction in egg laying were observed after treatment with JM-20. In the evaluation of locomotion and defecation behaviors in mutants with reduced levels of GABA (unc-25), the effect caused by JM-20 was abolished, suggesting the GABAergic modulation exerted by the compound. Additionally, JM-20 exhibited a similar effect to Diazepam in the observed behavioral parameters. Computational analysis revealed that JM-20 binds to the GABAA receptor site very similarly to Diazepam. In summary, this study provides a deeper understanding of the effects of JM-20 in C. elegans, highlighting its effects on the GABAergic system in this animal model.